Active fault and warning risk of subcidence-cracking hazard in mountain region of the Quang Ngai Province - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2012)
Mountainous region of Quang Ngai province in active tectonic activity; subcidence-cracking hazard takes place with increasing scale which is difficult to control, costing the lives of local residents. The establishment of active faults and the warning of subcidence-cracking hazard development planning for sustainable socio-economic development of Quang Ngai province is presented in this paper. - The distribution of major faults that sub parallel Tra Bong River, Tra khe-Tra Tan; sub longitude Dac Pong, Re River, Son Ha-Ba To; NE-SW Tra Binh-Di Lang, Tra No River and higher faults was studied for mountainous areas. - In the context of modern geodynamics compression according to the sub longitude, the tectonic stress field with maximum compression axis the sub meridian, the maximum rift axis sub parallel method, the fracture Dac Pong, Re River, Son Ha-Ba,... smooth operation - to slip by; Tra Binh-Di Lang, River pay,... active left-slip faults upon and Tra Bong River, Tra Khe-Tra Tan,... activities have slipped by. - Most of the points of subcidence-cracking hazard distributed along the Tra Bong River fault. Zone of dynamic effective of fault running the risk of subcidence-cracking highly distributed along fault and the Tra Bong River and Re River faults, in the range from 5-8 km of the western district of Tây Tra, Tra Bong, Son Ha and Ba To. Area of high risk of subcidence- cracking distributed along faults Dac Pong, Son Ha-Ba River and debt repayment, in the range of 2-3km to 5-7 km west of the district of Tay Tra, Son Tay and Son Ha District, east southern and western districts of Ba Tơ and Minh Long district. Area of average risk of subcidence- cracking the distribution along fault lines of Tra Binh Di Lăng, Tra Khê-Tra Tan with a width of 2-3km; Area of low risk of subcidence-cracking distributed along faults and the high level is very low risk of subcidence-cracking outside the region impact zone dynamics faults above activities.